Impedance Spectroscopy as a Methodology to Evaluate the Reactivity of Metakaolin Based Geopolymers - Sanches, Alex Otávio; Istuque, Danilo Bordan; Bortoletto, Marcelo; Malmonge, José Antônio; Soriano, Lourdes; Borrachero, María Victoria; Payá, Jordi; Tashima, Mauro M.; Akasaki, Jorge Luis (MPDI, 2022)
The aim of this study was to use the electrical impedance spectroscopy technique (IS) to carry out a systematic study on the mechanism of metakaolin geopolymerization for up to 7 curing days. The study was developed on two batches of metakaolin (MK), and their reaction processes were compared. Interpretative fundamental elements were developed based on the effective electrical conductivity curves regarding the metakaolin geopolymerization. X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) were previously carried out and used to interpret and validate the electrical behavior of the fresh and hardened MKbased geopolymer pastes. The results highlighted the sensibility of the impedance technique to the identification and description of the MK geopolymerization process, as well as the changes resulting from even slight variations in the metakaolin composition. Furthermore, this indicated that the geopolymerization process in highly alkaline solutions could be divided into seven stages, including the processes of dissolution, nucleation, precipitation and formation of the gel and, eventually, the retraction/microcracks constitution. Late dissolution processes could be observed during the more advanced stages and were attributed to particles not being fully hydrated.
Keywords: Geopolymer; Metakaolin; Impedance spectroscopy